Cases of fatal electrocution due to contact between carbon fibre fishing rods and overhead power lines - Szymon Rzepczyk; Paweł Świderski; Maciej Obst; Damian Rusek; Beata Bożek; Zbigniew Żaba; Czesław Żaba (Egyptian Journal of Forensic Sciences, 2024)
Abstract Background Electrocution caused by electricity conducted via overhead power lines carries a high risk to health and life. With the introduction and proliferation of conductive carbon fibre fishing tackle, severe and fatal electrocution occurs due to accidental contact with overhead transmission lines. Case presentation The paper presents three cases of men who died due to electrocution from a conductive fishing rod, which occurred in the same fishery over several years. The deaths occurred on the spot in two cases despite rapid rescue efforts. One of the men died in the hospital the following day due to developing severe complications. Additionally, all of the victims were under the influence of alcohol at the time of the incident. During postmortem diagnosis, skin lesions were identified as signs of electric shock on the hands and feet in each case. To the best of the authors’ knowledge, there is no similar case series available in the literature where several almost identical fatal electrocutions occurred in the same place as a result of contact of a fishing rod with overhead power lines. Conclusions Action is needed to avoid similar incidents and to increase safety in the vicinity of power lines.